Analysis of the usability of selected auction websites - Adrian Duwer; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
The selection and use of an e-commerce service can be conditioned by its properties such as ease of use, intuitiveness, productivity, offered functionalities, and aesthetic appeal. Within this study, the usability of three popular auction websites: eBay, Amazon, and Allegro, was examined. Selected interfaces of these websites and the ways in which users use them were analyzed. For this purpose, an experiment was prepared and conducted consisting of two parts: a survey and eye-tracking tasks. The obtained results indicate differences in usability among the websites. Suggestions provided by users show that despite the popularity of each of these well-known services, there are still some of their elements that require improvement and enhancement.